2021
DOI: 10.1016/j.ajog.2021.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019 infection and hypertensive disorders of pregnancy

Abstract: Objective The possible connection between COVID-19 and hypertensive disorders of pregnancy (HDP) remains unclear (1). Elucidating these outcomes is important both to better understand COVID-19 pathophysiology and to improve patient care in pregnant patients with COVID-19. Our objectives were to test the hypothesis that COVID-19 infection is associated with an increased risk of HDP and to examine the association between the gestational age at COVID-19 infection and delivery and HDP risk. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 5 publications
2
52
0
3
Order By: Relevance
“…Overall, 31.4% of patients with a COVID-19 during their pregnancy developed a HDP, compared to 13.3% of controls. Our results are consistent with the available literature 18,24 . While one meta-analysis 9 did not demonstrate this association, the studies included had heterogenous designs, different primary outcomes, and most lacked a control group.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Overall, 31.4% of patients with a COVID-19 during their pregnancy developed a HDP, compared to 13.3% of controls. Our results are consistent with the available literature 18,24 . While one meta-analysis 9 did not demonstrate this association, the studies included had heterogenous designs, different primary outcomes, and most lacked a control group.…”
Section: Discussionsupporting
confidence: 94%
“…Rosenbloom and Raghuraman (2021) found that a COVID-19 diagnosis conferred an approximate 2-fold risk of HDP (hazard ratio (HD) 1.93; CI 1.13-3.31) [24]. This was especially true if COVID-19 was diagnosed prior to 32 weeks' gestation, with the HR of 2.17 (CI 1.…”
Section: Discussionmentioning
confidence: 99%
“…Because COVID-19 has been shown to increase the risk for adverse pregnancy outcomes, including preeclampsia, 4 , 5 , 6 the concept of a COVID-19–associated preeclampsia-like syndrome, which includes similar placental pathology, has been proposed. 7 , 8 , 9 However, it is important to note that COVID-19 during pregnancy and preeclampsia share the same set of risk factors, namely preexisting hypertension, obesity, and diabetes. 10 , 11 , 12 Thus, the association between COVID-19 and preeclampsia could be confounded by common underlying risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, pregnant women with covid-19 are at increased risk of admission to an intensive care unit and are more likely to experience preterm birth [ 6 ]. There are growing arguments for an increased risk of fetal death (2) and hypertensive complications of pregnancy [ 7 ]. Intra-uterine growth restriction (IUGR) seems to be three times more frequent than in COVID negative patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%